2015
DOI: 10.1002/ab.21578
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive perfectionism's link to aggression and self‐harm: Emotion regulation as a mechanism

Abstract: The negative affect that results from negative feedback is a substantial, proximal cause of aggression. People high in maladaptive perfectionism, the tendency to focus on the discrepancy between one's standards and performance, are characterized by an exaggerated negative affective response to negative feedback. This exacerbated affective response to failure may then dispose them to hurt others and themselves as aggression and self-harm are often perceived as a means to regulate negative affect. In Study 1, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 56 publications
2
39
0
Order By: Relevance
“…We also found that the perceiving branch negatively correlated with the sub‐scales of hostility and physical aggression, while the managing branch negatively correlated with the sub‐scales of hostility, with physical and verbal aggression. In addition, supporting our third hypothesis and previous findings in the literature, we found NA to be positively correlated with total aggression and the four sub‐scales of the BPAQ (Chester et al, ; Ebesutani et al, ; Fettich et al, ; Shorey et al, ). Therefore, our results are in line with previous studies analysing EI and NA as risk and protective factors of aggression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We also found that the perceiving branch negatively correlated with the sub‐scales of hostility and physical aggression, while the managing branch negatively correlated with the sub‐scales of hostility, with physical and verbal aggression. In addition, supporting our third hypothesis and previous findings in the literature, we found NA to be positively correlated with total aggression and the four sub‐scales of the BPAQ (Chester et al, ; Ebesutani et al, ; Fettich et al, ; Shorey et al, ). Therefore, our results are in line with previous studies analysing EI and NA as risk and protective factors of aggression.…”
Section: Discussionsupporting
confidence: 91%
“…NA is defined as the extent to which a person reports feeling upset or unpleasantly aroused (Watson & Tellegen, ). The literature has revealed how higher levels of NA are related to higher aggression throughout the life span as well as in clinical and nonclinical populations (Chester, Merwin, & Dewall, ; Ebesutani, Kim, & Young, ; Fettich, Mccloskey, Look, & Coccaro, ; Megías, Gómez‐Leal, Gutiérrez‐Cobo, Cabello, & Fernández‐Berrocal, 2018; Shorey, McNulty, Moore, & Stuart, ). NA should be included at the second stage of the GAM as an individual negative internal state that can be influenced by the situational (or personal) variables of Stage 1 (e.g., exposure to violence; Ebesutani et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Since its validation as an aggression measure, the VDAT has proven effective at measuring aggression towards participants' children (McCarthy, Crouch, Basham, Milner, & Skowronski, 2016), marital partners (Bushman, DeWall, Pond, & Hanus, 2014), provocateurs (Chester, Merwin, & DeWall, 2015), and rejecters (Chester & DeWall, 2016, 2017. These findings demonstrate the VDAT's flexibility and the extent to which humans can readily bestow personhood upon a simple, virtual representation of a human-like doll.…”
Section: The Voodoo Doll Self-injury Taskmentioning
confidence: 85%
“…It asks participants to imbue an inanimate doll with features of actual individuals. This task has shown excellent reliability over time, corresponding to other measures of aggressive behavior and exhibiting appropriate responsiveness to laboratory provocations (Chester, Merwin, & DeWall, ; DeWall et al, ). The responses to the voodoo‐doll task do not signify “actual” aggression because the victim does not experience direct harm.…”
Section: Concepts Pertaining To Attitudes Towards National Ingroupsmentioning
confidence: 99%